Toward Retail Competition in the Portuguese Electricity Market - Ghazvini, Mohammad Ali Fotouhi (2016)
Portugal has opened its’ retail electricity market for new entrants, while removing the burdens for competition among the supplier and customers’ switching between the electricity suppliers. The ultimate objective of this liberalization practice is to sharpen competition in the retail segment of the electricity market. In this paper, we assess the success of the liberalization process in the retail sector of the Portuguese electricity market by studying the customers’ behavior, changes in the retail rates and the market concentration. Finally, we provide some explanations for the high switching rates of the customers despite the increase in the retail rates. We also explain why the retail rates are not following the changes of the wholesale prices and the reason for the high market concentration in the retail segment.